Weight-Related People-First Language Use and Visual Content Analysis of Images from the Online Coverage of the 2018 Presidential Physical Exam (P04-180-19). (13th June 2019) - Klobodu, Seth; Bailey, Dylan; Johnson, Levi; Carroll, Sydney; Merrick, Courtney
Abstract: Objectives: Weight-related stigmatization is pervasive in American society with health and social consequences. The public increasingly gets news online and it can influence how they understand health issues, including obesity. Online media has a wide reach and can perpetuate the social acceptability of weight stigma through language and visual content. To combat weight bias, experts recommend the use of People-First Language (PFL) and avoidance of stigmatizing images by the media. Research has not yet analyzed the use of weight-related PFL or images in online coverage of any presidential physical exam. Our first objective was to determine the prevalence of PFL in online news coverage of the 2018 presidential physical exam. Our second objective was to examine the images that accompanied the online coverage. Methods: Google search engine was used to identify all US based online news articles that covered the physical exam between December 7, 2017 and February 17, 2018. Articles meeting inclusion criteria were coded for the presence of weight-related language keywords and use of PFL. We then performed a content analysis on the images that accompanied the online news articles. Four coders systematically reviewed the visual content to capture images that may be stigmatizing. Simple descriptive statistics were used to summarize data. Results: Exactly 1242 articles were obtained based on keyword searches and 376 met inclusion criteria. After excluding duplicates, 179 articles were included in the final analysis. Use of PFL was observed in 2% (4 of 179 articles) of coverage. Use of the adjective "obese" occurred in 44% of coverage, the condition "obesity" in 19% of coverage and "overweight" in 37% of coverage. About 28% (64 of 227) of images portrayed the president as exercising, but of those, 84% (54 of 64) were portrayed in a stigmatizing way. Of 227 photographs of the president accompanying the online news coverage, 37% (83 of 227) were portrayed in a negative and stigmatizing manner. Conclusions: Prevalence of weight-related PFL was low and use of stigmatizing images was noticeable. Exercise should display positive characteristics in an image. However, in our study it was counterintuitively used for stigmatizing portrayals. Future research should identify factors surrounding the lack of PFL and use of stigmatizing images by online news media. Funding Sources: LJ received funding from the U.S. Dept. of Education HSI STEM grant.